Comparing Hospital Staff Nutrition Knowledge, Attitudes, and Practices Before and 1 Year After Improving Nutrition Care: Results From the More‐2‐Eat Implementation Project. Issue 4 (19th December 2017) - Laur, Celia V.; Keller, Heather H.; Curtis, Lori; Douglas, Pauline; Murphy, Joseph; Ray, Sumantra
Abstract: Background : Staff play key roles in the prevention, detection, and treatment of hospital malnutrition. Understanding staff knowledge, attitudes, and practices (KAP) is important for developing and evaluating change management strategies. Methods : The More‐2‐Eat project improved nutrition care in 5 Canadian hospitals by implementing the Integrated Nutrition Pathway for Acute Care (INPAC). To understand staff views before (T1) and after 1 year of implementation (T2), a reliable KAP questionnaire, based on INPAC, was administered. T2 included questions about involvement in implementation. The mean difference between T2 and T1 responses was calculated, and t tests were used for comparisons. Results : The questionnaire was completed at T1 (n = 189) and T2 (n = 147) (unpaired); 57 staff completed both questionnaires (paired). A significant increase in total score was seen in unpaired results at T2 (from 93.6/128 [range, 51–124] to 99.5/128 [range, 54–119]; t = 5.97, P < .0001), with an increase in knowledge/attitudes (KA) ( t = 2.4, P = .016) and practice ( t = 3.57, P < .0001) components. There were no statistically significant changes in paired responses. Seventy percent (n = 102/147) noticed positive changes in practices, 12% (n = 18) noticed positive/negative changes, 1% (n = 1) noticed negative change, and 17% (n = 25) noticed no change. Fifty‐nine percent (n = 86) felt involved in the change, and these staff had higher KA and KAP scores than those who did not feel involved. Conclusion : Staff involvement is important in the implementation process for improving nutrition care.